(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Currently, the issue of early diagnosis of coronary heart disease (CHD) remains the most urgent task of cardiology. Gas analysis method for analysis of exhaled air (BB) is a new approach to solving this problem [5].